Upaya Pencegahan Penyalahgunaan Obat Penenang Golongan Psikotropika: Kajian Regulasi dan Praktik di Lapangan - Salmi, Salmi; Nurdin , Ilham B; Subair, Laola (Indonesian Journal Publisher, 2025)
This study aims to analyze efforts to prevent the abuse of psychotropic drugs and identify obstacles in their implementation. A qualitative method with a normative-empirical approach was used, examining relevant regulations and their application in the field. Data were collected through interviews with law enforcement officers, medical personnel, former abusers, document studies, research reports, scientific articles, and government publications. The findings indicate that psychotropic abuse remains widespread due to low public awareness, weak distribution supervision, and limited rehabilitation facilities. Prevention efforts include public education on the dangers of psychotropics, law enforcement against abusers and illegal drug trafficking, and rehabilitation for individuals suffering from addiction. However, the effectiveness of these measures is hindered by a lack of community participation and inadequate infrastructure, despite sufficient funding. To optimize prevention and intervention efforts, synergy among law enforcement agencies, rehabilitation institutions, medical professionals, and community organizations is essential. Recommended strategies include advocacy, social support, partnerships, and community empowerment. The National Narcotics Agency of South Sulawesi plays a crucial role in these efforts through direct and indirect communication, advocacy, and the formation of anti-drug activist groups to strengthen community involvement in combating psychotropic abuse.